SPIRITUAL ENTERPRENERSHIP WARISAN SUNAN KUDUS: MODAL BUDAYA PENGEMBANGAN EKONOMI SYARI’AH DALAM MASYARAKAT PESISIR (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2014)
This paper will prove a thesis that, in a religious community culture was influenced by three phenomena; modernity, religion and culture of ancestors. That case also happen especially in Kudus in strengthening of spiritual enterprenership that was known as gusjigang as Sunan Kudus’ heritages. This paper analyzed by ethnoarchaeology combined with a semitic approach. Sunan Kudus predicates which, among other known as waliyyul ilmy and also as an Islamic merchants has spawned a cultural communication that reproduces gusjigang culture (bagus/ noble-character, ngaji/ scientific orientation, dagang/ entrepreneurship). Gusjigang culture is part of a local genius who planted by Sunan Kudus is so relevant enough to be developed as the basis of spiritual entrepreneurship or religious capitalism in the coastal areas. The development of Shariah economic studies and also its implementation in order to find a clear distinction needs to pay attention to social and cultural foundation such as the spirit of religious capitalism, that is guided by the principles, values, and religious ethics are built on the basis of justice and goodness (al-Adl wa'l ihsan) to humanity. In some cases gusjigang culture in Kudus in line with spiritual entrepreneurship ethos and the spirit of religious capitalisme.Paper ini akan membuktikan tesis bahwa budaya masyarakat agama dipengaruhi oleh tiga fenomena yaitu; modernitas, agama dan budaya nenek moyang. Gejala tersebut juga terjadi di Kudus dalam penguatan spiritual enterprenership yang dikenal dengan gusjigang sebagai warisan Sunan Kudus. Pembahasan tulisan ini dianalisis dengan pendekatan etnoarkeologi dikombinasikan dengan pendekatan Semiotik. Predikat Sunan Kudus yang dikenal sebagai waliyyul ilmy dan juga sebagai pedagang Islam telah melahirkan komunikasi budaya yang mereproduksi budaya gusjigang (baGus, ngaJi, daGang). Budaya Gusjigang merupakan bagian dari kearifan lokal yang ditanamkan oleh Sunan Kudus begitu relevan sebagai dasar pengembangan spiritual enterprenership atau kapitalisme religius di daerah pesisir. Perkembangan studi ekonomi syariah dan juga implementasinya yang distingtif perlu memperhatikan modal sosial dan budaya seperti semangat kapitalisme religius, yang dipandu oleh prinsip-prinsip, nilai-nilai, dan etika universal Islam seperti nilai-nilai keadilan dan kebaikan (al-Adl wal ihsan) bagi umat manusia. Dalam kasus tertentu, budaya gusjigang di Kudus sejalan dengan etos kewirausahaan spiritual dan semangat kapitalisme agama sehingga hal ini bisa dijadikan sebagai landasan budaya dalam membumikan ekonomi syari’ah di pesisir ini.Kata Kunci: Spiritual entrepreneurship, Sunan Kudus, gusjigang, religious capitalism